Does substituting reprotoxic solvents during ultrafiltration membrane fabrication really mitigate environmental impacts? Focus on drinking water production - Prézélus, Flavie; Remigy, Jean-Christophe; Guigui, Christelle; Tiruta-Barna, Ligia (Journal of cleaner production, 2022)
The purpose of this research is to fill knowledge gaps on the relevance of solvent substitution from a life cycle perspective and to put forth relevant operating conditions for possible process optimisation and eco-design. Solvents commonly used to prepare ultrafiltration membranes for drinking water applications are indeed identified by the European REACH regulation for their potential reproductive toxicity and are the subject of research as regards their substitution. Coupling Life Cycle Assessment (LCA) with process modelling allowed to compare conventional membranes (cellulose triacetate as polymer, NMP as solvent) to biosourced membranes (cellulose diacetate as polymer, methyl lactate as solvent). Although methyl lactate fabrication leads to lower environmental scores than NMP fabrication (32% and 10% less GWP100 and ReCiPe Endpoint, respectively), LCA scores for membrane fabrication are similar (1.9 points ReCiPe for 1 m2 membrane) or slightly different, i.e. 11 kg CO2-eq and 9.4 kg CO2-eq for 1 m2 of conventional and biosourced membrane, respectively. From an environmental point of view, solvent substitution has little influence on impacts. Rather, environmental hotspots lie in the operation stage, with impact scores about 10,000 times higher than those of membrane fabrication, which holds out considerable prospects for the optimisation of operating conditions on drinking water plants. [Display omitted] •Solvent substitution does not bring about any significant environmental mitigation.•Coupled process modelling-LCA is an agile tool for process evaluation and eco-design.•Lower environmental impacts of methyl lactate fabrication compared to NMP solvent.•Extensive filtration operation mitigates overall impacts.